KARAKTERISASI SIFAT BAJA TULANGAN BETON PRATEKAN UNTAIAN KAWAT (WIRE STRAND) - Bumulo, Ronny
Nowdays wire strand (7-wires) reinforced steel of prestressed concrete are commonly used for any application for construction such as bridge with long distance abutment, multilevel building, harbour and industrials construction. The increasing usage of this application must be supported also with high quality materials, and the ability to fabricate a domestic product. The research carried out to VSL-System wire strand reinforced steel of prestressed concrete had a nominal diameter of 12.7 mm (consisted of one straight wire which had a diameter of 4.4 mm in the center and six twisted wires with diameter of 4.2 mm) is a laboratory research to study its microstructure and its mechanical properties (such as tensile strength, yield strength, and ductility). The wire strand reinforced steel of prestressed concrete is compared with a wire rod eutektoid steel with a diameter of 5.7 mm an imported product (Bekaert) and reinforced steel of non-prestressed concrete with a diameter of 10.00 mm from PT.Krakatau Steel (KS). Optical metallography and Scanning Electron Microscopy (SEM) examination of the ? 4.4 mm straight wire and ? 4.2 mm twisted wire of as it is and annealed condition ones showed that both wire had a microstructure of fine pearlite, which is strong and ductile. This microstructure is the same as the microstructure of an imported product of the ? 5.7 mm wire rod eutektoid steel. The tensile strength of the ? 4.4 mm straight wire of as it is condition from tention test with Instron machine 1195 was 2227 MPa, and its elongation and reduction of area were 4.7 % and 24.6 %, respectively. A prediction calculation about tensile strength from hardness test data on the ? 4.4 mm as it is straight wire gave a lower value, i.e. 1732 MPa. This difference is predicted caused by a texture strenghtening of that reinforced steel of prestressed concrete in longitudinal direction. Theoritical calculation of ultimate strenght based on Heller formula by measuring the interlamellar spacing of pearlite, mean pearlite collonies diameter, and fraction of ferrite in SEM photograph gave a much lower value, i.e. 794 MPa. This value can not be considered in practical usage, because this formula needs a series of measurement of interlamellar spacing of pearlite (50 times) and this formula is only valid for isotropic material.